2021
DOI: 10.1111/jocd.13892
|View full text |Cite
|
Sign up to set email alerts
|

A clinical evaluation of noninvasive and contactless radiofrequency technique in the treatment of abdominal fat

Abstract: Background There is an increasing demand for fat reduction and body contouring procedures. Noninvasive radiofrequency devices have been used to tighten skin and treat cellulite, but there are few studies confirming their efficacy for abdominal fat reduction. Objective This study explored the effects of four noninvasive radiofrequency (RF) treatments on abdominal fat in Asian subjects, evaluating body weight, body mass index (BMI), and waist circumference. Methods In this study, 16 patients with abdominal obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…In another study, Winter performed a prospective self‐controlled study and observed a reduction in circumference, and skin laxity improvement could also be effectively achieved using a combination of RF, infrared, and mechanical manipulation 27 . Our findings are consistent with the results obtained by Qin et al, which indicated that non‐invasive and contactless selective RF methods were effective and safe in the reduction of fat, BMI, and abdominal circumference 28 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In another study, Winter performed a prospective self‐controlled study and observed a reduction in circumference, and skin laxity improvement could also be effectively achieved using a combination of RF, infrared, and mechanical manipulation 27 . Our findings are consistent with the results obtained by Qin et al, which indicated that non‐invasive and contactless selective RF methods were effective and safe in the reduction of fat, BMI, and abdominal circumference 28 …”
Section: Discussionsupporting
confidence: 90%
“…27 Our findings are consistent with the results obtained by Qin et al, which indicated that non-invasive and contactless selective RF methods were effective and safe in the reduction of fat, BMI, and abdominal circumference. 28 Fajkošová et al reported that a selective RF system is a painless, safe, and effective treatment for body contouring and circumferential fat. 29 Several other studies have also confirmed the effectiveness of RF as a non-invasive technique in the reduction of subcutaneous fat in the thighs and buttocks.…”
Section: Ta B L E 1 Demographic and Baseline Data Of Participantsmentioning
confidence: 99%
“…Based on the review of evidence presented earlier, radiofrequency is most used in the abdominal region and results in a statistically significant decrease in abdominal fat thickness. 32,34,36,[38][39][40] These outcomes continue to improve with each treatment and persist until the last follow-up appointment. Additionally, this method has shown to successfully reduce fat volume in the lower face, both in terms of submental circumference and fat thickness.…”
Section: Clinical Efficacymentioning
confidence: 83%
“…The main side effects of radiofrequency treatment were heat sensation, mild pain or discomfort and local skin irritation, that is, erythema, warmth, tingling or oedema. [32][33][34][37][38][39][40] interruption of treatment 34 and one participant developed a palpable nodule. 40 All adverse reactions were transient and resolved without intervention.…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation